2021
DOI: 10.1371/journal.pone.0251192
|View full text |Cite
|
Sign up to set email alerts
|

‘If relevant, yes; if not, no’: General practitioner (GP) users and GP perceptions about asking ethnicity questions in Irish general practice: A qualitative analysis using Normalization Process Theory

Abstract: Context The use of ethnic identifiers in health systems is recommended in several European countries as a means to identify and address heath inequities. There are barriers to implementation that have not been researched. Objective This study examines whether and how ethnicity data can be collected in Irish general practices in a meaningful and acceptable way. Methods Qualitative case study data generation was informed by Normalization Process Theory (NPT) constructs about ‘sense’ making and ‘engagement’. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…A majority of donors indicated that they found an ethnic‐ancestry option they were happy with (91.3%). When asked to indicate how easy it was to find an ethnic‐ancestry the were happy with, respondents reported a median score of 8 8–10 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of donors indicated that they found an ethnic‐ancestry option they were happy with (91.3%). When asked to indicate how easy it was to find an ethnic‐ancestry the were happy with, respondents reported a median score of 8 8–10 …”
Section: Resultsmentioning
confidence: 99%
“…When asked to indicate how easy it was to find an ethnic-ancestry the were happy with, respondents reported a median score of 8. [8][9][10] Only 43 donors (8.4%) reported that they did not find an acceptable ethnic-ancestry option. Of these, 11 reported their reason was having to select 'other' and write in their ethnic-ancestry, five reported not knowing their ethnic-ancestry, and 30 reported it was 'something else' with 28 providing a qualitative response.…”
Section: Finding An Ethnic-ancestry Option They Are Happy Withmentioning
confidence: 99%
See 1 more Smart Citation
“…The historical harm of treating ‘race’ as having a biological basis and the potential for using ‘race’ to discriminate has led to hesitations or misperceptions for collecting data about patients’ ‘race’ or ‘ethnicity’ 9 10. For instance, healthcare providers perceive barriers to collecting demographic data, such as privacy and legal concerns, possible resistance from patients and staff, and difficulty recording the data 11–13. These attitudinal and practical barriers have led to the lack of clinic guidelines and less data collection.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 5 Furthermore, in a recent qualitative study, Irish general practitioners raised fundamental doubts about its clinical relevance for individual consultations. 6 An additional reserve relates to the multifaceted concept of ethnicity, challenging sufficiently unambiguous operationalization. 7 This may all add to the catch-22 in the debate on health disparities: lack of clarity on the clinical relevance of ethnic identifiers impedes their further study, prohibiting in-depth understanding of their potential role in closing health disparity gaps.…”
mentioning
confidence: 99%